MrkH, a novel c-di-GMP-dependent transcriptional activator, controls Klebsiella pneumoniae biofilm formation by regulating type 3 fimbriae expression - Wilksch,JJ; Yang,J; Clements,A; Gabbe,JL; Short,KR; Cao,H; Cavaliere,R; James,CE; Whitchurch,CB; Schembri,MA; Chuah,MLC; Liang,Z-X; et al. (PLOS Pathogens, 2011)
Klebsiella pneumoniae causes significant morbidity and mortality worldwide, particularly amongst hospitalized individuals. The principle mechanism for pathogenesis in hospital environments involves the formation of biofilms, primarily on implanted medical devices. In this study, we constructed a transposon mutant library in a clinical isolate, K. pneumoniae AJ218, to identify the genes and pathways implicated in biofilm formation. Three mutants severely defective in biofilm formation contained insertions within the mrkABCDF genes encoding the main structural subunit and assembly machinery for type 3 fimbriae. Two other mutants carried insertions within the yfiN and mrkJ genes, which encode GGDEF domain- and EAL domain-containing c-di-GMP turnover enzymes, respectively. The remaining two isolates contained insertions that inactivated the mrkH and mrkI genes, which encode for novel proteins with a c-di-GMP-binding PilZ domain and a LuxR-type transcriptional regulator, respectively. Biochemical and functional assays indicated that the effects of these factors on biofilm formation accompany concomitant changes in type 3 fimbriae expression. We mapped the transcriptional start site of mrkA, demonstrated that MrkH directly activates transcription of the mrkA promoter and showed that MrkH binds strongly to the mrkA regulatory region only in the presence of c-di-GMP. Furthermore, a point mutation in the putative c-di-GMP-binding domain of MrkH completely abolished its function as a transcriptional activator. In vivo analysis of the yfiN and mrkJ genes strongly indicated their c-di-GMP-specific function as diguanylate cyclase and phosphodiesterase, respectively. In addition, in vitro assays showed that purified MrkJ protein has strong c-di-GMP phosphodiesterase activity. These results demonstrate for the first time that c-di-GMP can function as an effector to stimulate the activity of a transcriptional activator, and explain how type 3 fimbriae expression is coordinated with